Education Through Animated Videos Increases Adolescent Girls Knowledge of Sexual Violence Based on Law No. 12 of 2022 - Pont, Anna Veronica; Kaparang, Mercy Joice; Yanti M., Riska; Nurfatimah, Nurfatimah; Taqwin, Taqwin (Poltekkes Kemenkes Palu, 2025)
Sexual violence against adolescent girls is a global issue with high prevalence and diverse forms. In Palu City, Central Sulawesi, Indonesia, this problem is critical. This study assesses the impact of educational interventions using animated videos on adolescent girls' knowledge of sexual violence based on Law No. 12 of 2022. A pre-experimental, pretest-posttest one-group design was conducted from May 7-15, 2024, with 50 class X students from SMAN 5 Palu selected through stratified random sampling. The intervention was animated video counseling, and the outcome was knowledge of sexual violence. Data were collected via questionnaires and analyzed using the Wilcoxon test at a 95% confidence level. Before the intervention, 80% of respondents had insufficient knowledge about sexual violence. Post-intervention, 74% had good knowledge, with only 4% remaining insufficient. The Wilcoxon test confirmed the intervention's effectiveness (Z = -6.125, p < 0.000). The study demonstrates the efficacy of animated video education in enhancing understanding of sexual violence among adolescent girls. The improvement in knowledge supports using audiovisual media in educational interventions for sensitive topics. Animated video educational interventions significantly improve knowledge of sexual violence among adolescent girls and should be widely implemented in schools. Future research should use larger samples and qualitative methods to explore the intervention's impact further.